A Young Male with Spontaneous Ruptured Cerebral Arteriovenous Malformation (Case Report) - Santos, Vitorino M.; Flores, Leandro P.; Barros, Isabella A.; Faria, Priscilla S.; Lamounier, Carolina P.; Casasanta, Renata A. (BALI MEDICAL JOURNAL, 2016)
Background: Cerebral arteriovenous malformation (AVM) is considered a congenital condition characterized by arterial-venous connections in the absence of intermediate capillaries with circulatory and functional changes, inclusive on the cerebrospinal fluid (CSF) dynamics. Case: A previously healthy young man with abrupt onset of intense headache followed by incoercible vomiting and generalized tonic-clonic seizures. On admission, he was in Glasgow scale IV with respiratory gasping, signs of decerebration and anisocoric mydriasis, and right paresis. Computed tomography showed left intraparenchymal hematoma and intraventricular blood. The abnormal vessels and blood clots were removed by neurosurgery. In early postoperative phase a large cerebrospinal fluid leak developed, and was aspirated and further controlled. The patient had respiratory complications, including pulmonary infection by Pseudomonas. Conclusions: After longstanding hospitalization, he was referred to other medical institution and home care.